PENERAPAN HUKUM TERHADAP AHLI WARIS PENGGANTI BERDASARKAN HUKUM ISLAM DI SAMARINDA - Chairil Anwar (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACT This thesis is the result of a study entitled “Application Of  Law Against Substitute Heirs Based on Islamic Law in Samarinda”. This study aims to address the following issues: (1) How is the application of the law to substitute heirs based on Islamic law (2) What are the reasons underlying the enactment of the successor heirs. This type of research is a legal research with normative juridical approach method, namely legal research conducted by prioritizing examining library materials or document called secondary data, in the from of primer, and secondary legal materials. The research specification is descriptive, which aims to provide and overview carried out using qualitative methods from legal theories and legal doctrines and the opinions of Islamic legal expert. The results of the research carried out it can be concluded that based on article 185 of the compilation of Islamic law that the replacement of heirs can occur in the straight down line or a straight line to the side, whit a portion no larger than the heirs he replaced. A surrogate heirs occur when the heirs has passed away first from an heirs, and must have a legitimate nasab ( offspring ) with the testator. Keywords : Islamic Inheritance law, Civil Code Inheritance Law, Subsitusite Heirs.